Analytical and numerical evaluation of quarter-elliptic-braced steel moment frames (QEB-MFs). (March 2023) - Fanaie, Nader; Shirpour, Alireza
Abstract: Concentrically braced frames (CBFs) have an excellent performance to the lateral seismic forces at the time of the mild earthquakes, but they are weak under severe seismic loads due to the occurrence of buckling of the bracing members and the lack of proper ductility in terms of energy absorption and do not behave properly. This article introduces the new quarter-elliptic brace. Adding this brace to the moment frame improves the stiffness of this system and impedes the excess structural deformation in this system. In the present study, a precise analytical formulation is presented using the concept of strain energy and Castigliano's theorem in order to calculate the elastic lateral stiffness of a two-dimensional single-span and single-story steel moment frame equipped with quarter-elliptic brace. In this relation, all effective factors, including axial and shear forces as well as bending moment, were considered for all frame members. The proposed formulation was controlled by the results of various examples in OpenSees software. The error percentage between the results obtained from the newly developed formulation and numerical analysis of finite elements is very insignificant so that it can be ignored. Also, the seismic performance of this system was investigated according to the FEMA P695 methodology for near-field and far-field ground motion records compared with the intermediate moment frame. The results showed that using a quarter-elliptic brace in the intermediate moment frame improves the seismic performance of this system.